GREEN ECONOMY DAN CIRCULAR ECONOMY SEBAGAI STRATEGI PEMBANGUNAN EKONOMI BERKELANJUTAN DI INDONESIA - Gisela Anantasia; Muhammad Anasrullah (CV. Adiba Aisha Amira, 2026)
Indonesia’s economic development has achieved relatively stable growth over recent decades; however, it has also generated increasingly complex environmental and social challenges. Environmental degradation, excessive exploitation of natural resources, rising carbon emissions, and social inequality indicate that conventional growth-oriented economic development is no longer sustainable. Therefore, a paradigm shift toward development models that integrate economic, environmental, and social dimensions is urgently needed. This article aims to examine the role of the green economy and circular economy as strategic approaches to sustainable economic development in Indonesia. This study employs a qualitative research method using a literature review approach by analyzing academic journals, government policy documents, and reports from national and international institutions. The findings indicate that the implementation of green economy and circular economy principles can improve resource efficiency, reduce environmental impacts, and create inclusive and sustainable economic opportunities. Nevertheless, their implementation in Indonesia still faces challenges related to regulatory frameworks, financing, and human resource readiness. Thus, integrated policies and multi-stakeholder collaboration are required to strengthen the transition toward sustainable economic development.